The effects of photoperiod and temperature-related factors on maize leaf number and leaf positional distribution in the field - Xu, Honggen; Ming, Bo; Wang, Keru; Xue, Jun; Hou, Peng; Li, Shaokun; Xie, Ruizhi (Frontiers in Plant Science, 2023)
Quantifying the effects of various environmental conditions on maize leaf number is essential to understanding the environmental adaptations and population structure of maize plants and for enhancing maize productivity. In this study, seeds of three temperate-adapted maize cultivars, each belonging to different maturity classes, were sown on eight different dates. Sowing dates ranged from the middle of April to early July, which allowed us to cover a wide range of environmental conditions. Random forest regression and multiple regression models with variance partitioning analyses were used to assess the effects of environmental factors on the number of leaves and their distributions on maize primary stems. We demonstrated that the total leaf number (TLN) increased in the three cultivars in the following order: FK139 < JNK728 < ZD958, and variations in TLN for each cultivar were 1.5, 1.76, and 2.75 leaves, respectively. The variation in TLN was ascribed to changes in LB (leaf number below the primary ear), which were higher than variations in LA (leaf number above the primary ear). Variations in TLN and LB were mainly affected by the photoperiod during growth stages V7 to V11, and differences in TLN and LB in response to different photoperiods ranged from 1.34 to 2.95 leaves h-l. Variations in LA was mainly affected by temperature-related factors. Therefore, the results of this study enhanced our current understanding of key environmental conditions that affect maize leaf numbers, and provides scientific support for the benefits of adjusting sowing dates and selecting suitable cultivars to mitigate the effects of climate change on maize production.